On Spatial Distribution of Short Gamma-Ray Bursts from Extragalactic Magnetar Flares - Heon-Young Chang; Hee Il Kim (Journal of Astronomy and Space Sciences, 2002)
Recently, one interesting possibility is proposed that a magnetar can be a progenitor of short and hard gamma-ray bursts (GRBs). If this is true, one may expect that the short and hard GRBs, at least some of GRBs in this class, are distributed in the Euclidean space and that the angular position of these GRBs is correlated with galaxy clusters. Even though it is reported that the correlation is statistically marginal, the observed value of <V/Vmax> deviates from the Euclidean value. The latter fact is often used as evidence against a local extragalactic origin for short GRB class. We demonstrate that GRB sample of which the value of <V/Vmax> deviates from the Euclidean value can be spatially confined within the low value of z. We select very short bursts (T90<0.3 sec) from the BATSE 4B catalog. The value of <V/Vmax> of the short bursts is 0.4459. Considering a conic-beam and a cylindrical beam for the luminosity function, we deduce the corresponding spatial distribution of the GRB sources. We also calculate the fraction of bursts whose redshifts are larger than a certain redshift {z'}, i.e. f> z'. We find that GRBs may be distributed near to us, despite the non-Euclidean value of <V/Vmax>. A broad and uniform beam pattern seems compatible with the magnetar model in that the magnetar model requires a small zmax.